Use of radar detectors to track attendance of albatrosses at fishing vessels. Issue 1 (11th September 2017) - Weimerskirch, H.; Filippi, D.P.; Collet, J.; Waugh, S.M.; Patrick, S.C.
Abstract: Despite international waters covering over 60% of the world's oceans, understanding of how fisheries in these regions shape ecosystem processes is surprisingly poor. Seabirds forage at fishing vessels, which has potentially deleterious effects for their population, but the extent of overlap and behavior in relation to ships is poorly known. Using novel biologging devices, which detect radar emissions and record the position of boats and seabirds, we measured the true extent of the overlap between seabirds and fishing vessels and generated estimates of the intensity of fishing and distribution of vessels in international waters. During breeding, wandering albatrosses (Diomedea exulans) from the Crozet Islands patrolled an area of over 10 million km 2 at distances up to 2500 km from the colony. Up to 79.5% of loggers attached to birds detected vessels. The extent of overlap between albatrosses and fisheries has widespread implications for bycatch risk in seabirds and reveals the areas of intense fishing throughout the ocean. We suggest that seabirds equipped with radar detectors are excellent monitors of the presence of vessels in the Southern Ocean and offer a new way to monitor the presence of illegal fisheries and to better understand the impact of fisheries on seabirds. Abstract : Article impact statement : New logger fitted on threatened albatrosses detects and locates radar emissions of boats to estimate fisheries extent in the Southern Ocean.